Can the parasitic weeds Striga asiatica and Rhamphicarpa fistulosa co-occur in rain-fed rice? - Kabiri S; Rodenburg, J.; Kayeke J; Ast, A. van; Makokha, D.W.; Msangi SH; Irakiza, R.; Bastiaans, L. (Wiley, 2015)
Striga asiatica and Rhamphicarpa fistulosa are important parasitic weeds of rain-fed rice, partly distributed in similar regions in sub-Saharan Africa (SSA). It is not evident whether their ecologies are mutually exclusive or partially overlapping. In Kyela, a rice-growing area in south Tanzania where both parasites are present, three transects of about 3 km each across the upland–lowland continuum were surveyed in June 2012 and 2013. A total of 36 fields were categorised according to their position on the upland–lowland continuum as High, Middle or Low and soil samples were taken. In each field, parasitic and non-parasitic weed species were identified in three quadrats. Additionally, in two pot experiments with four different moisture levels ranging from wilting point to saturation, influence of soil moisture on emergence and growth of parasites was investigated. Striga asiatica was observed in higher lying drier fields, while R. fistulosa was observed in the lower lying wetter fields. Furthermore, non-parasitic weed species that were exclusive to S. asiatica-infested fields are adapted to open well-drained soils, while species that were exclusive to R. fistulosa fields are typical for wet soils. The experiments confirmed that S. asiatica is favoured by free-draining soils and R. fistulosa by waterlogged soils. These results imply that changes in climate, specifically moisture regimes, will be crucial for future prevalence of these parasitic weeds. The non-overlapping ecological range between their habitats suggests that their distribution and associated problems might remain separate. Thus, management strategies can be focused independently on either species.